Energy and water budget of rice under different establishment methods - Padma, Sayam; Vijayakumar, S; Venkatanna, B; Srinivas, D; Murugaiyan, Varunseelan; Kumar, R Mahender; Kuchi, Surekha; Mahadevappa, SG; Sundaram, Raman Meenakshi; Rekha, K Bhanu; Yakadri, M (ORYZA-An International Journal of Rice, 2023)
A field study aimed to investigate the influence of different rice establishment methods on energy and water budget of rice was conducted during kharif season of 2022. The experiment was carried out using a randomized block design with three replications. Seven treatments were examined, including three transplanting methods viz., SRI, mechanical transplanting and conventional transplanting, and four direct seeded rice (DSR) methods viz., wet DSR (drum seeding), wet DSR (broadcasting), dry converted wet rice (broadcasting) and dry converted wet rice (line sowing). Results revealed that chemical fertilizers, irrigation water, land preparation and seeding or transplanting operations constituted ~80% of the input energy in all rice establishment methods. Among the rice establishment methods, conventional transplanting exhibited the highest input energy of 21723.9 MJ ha-1, while dry converted wet rice (line sowing) recorded the lower input energy of 18394.3 MJ ha-1. In terms of output energy, wet DSR (drum seeding) recorded the highest value of 141781.1 MJ ha-1, whereas dry converted wet rice (broadcasting) registered the lowest value of 77223.2 MJ ha-1. The output energy of wet DSR (drum seeding) was comparable to that of SRI and dry converted wet rice (line sowing). Similarly, dry converted wet rice (line sowing) exhibited higher irrigation water productivity (0.73 kg m-3) and total water productivity (0.30 kg m-3) with a reduced water requirement of 630 mm. Compared to conventional transplanting, input energy consumption and irrigation water requirement was lower by 18.1% and 51.9% in dry converted wet rice (line sowing), 17.4% and 51.9% in dry converted wet rice (broadcasting), 16.9%, 36.7% in SRI and 9.13%, 27.6% in wet DSR (drum seeding) respectively. Thus, the adoption of wet DSR (drum seeding), SRI and dry converted wet rice (line sowing) is recommended for energy and water efficient rice production in Telangana.